2003
DOI: 10.4049/jimmunol.171.8.3947
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Enhanced Transcription of the IL-10 Gene in T Cells, Upon Contact with Human Glioma Cells, by Fas Signaling Through a Protein Kinase A-Independent Pathway

Abstract: Elevated expression of IL-10 has been frequently observed in tumor tissues and tumor-infiltrating cells. We show herein that transcription of the IL-10 gene in primary peripheral T cells and T cell lines is up-regulated upon contact with glioma cells without an induction of apoptosis in those T cells. Glioma-associated IL-10 induction was suppressed by interrupting the engagement of Fas and its ligand (Fas-L) with the antagonistic Ab, ZB4, by reducing Fas-L expression of glioma cells using the Fas-L-specific r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
2
7
0
1
Order By: Relevance
“…This result is consistent with a PKA-independent pathway of inhibitory signaling through DP, which has previously been reported in DCs (25). In primary human T cells and macrophages, gene expression and phagocytosis can also be regulated by exchange protein activated by cAMP (Epac), a downstream element of the cAMP pathway that is independent of PKA activation (55)(56)(57). A similar mechanism may also be involved in PGD 2 -induced inhibition of NK cell functions, which will require further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with a PKA-independent pathway of inhibitory signaling through DP, which has previously been reported in DCs (25). In primary human T cells and macrophages, gene expression and phagocytosis can also be regulated by exchange protein activated by cAMP (Epac), a downstream element of the cAMP pathway that is independent of PKA activation (55)(56)(57). A similar mechanism may also be involved in PGD 2 -induced inhibition of NK cell functions, which will require further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…To further determine whether PKA is the kinase that primarily mediates EGFRvIII stimulation of p-S of Dock180, we treated SNB19/parental, SNB19/EGFRvIII, LN444/parental and LN444/EGFRvIII cells with or without PKA inhibitors H-89 or KT5720. 19,20 Compared with the control, treatments with both PKA inhibitors markedly attenuated EGFRvIII stimulation of p-S of Dock180, p-Erk1/2, p-Akt, Rac1 activity and cell migration as well as cell proliferation (Fig. 2B to 2E, respectively).…”
Section: Resultsmentioning
confidence: 93%
“…For example, tumor-infiltrating lymphocytes (TILs) 3 are able to express vascular endothelial growth factor, which enhances angiogenesis in tumor regions (2,3). Recently, we have demonstrated that coculture with glioma cells will induce transcription of the IL-10 gene in T cells through Fas signaling (4). These findings support the hypothesis that tumors may highjack accumulated TILs to create a tumor growth-promoting environment; this event occurs by the evasion of immune surveillance using elevated local IL-10 production and increased angiogenesis by vascular endothelial growth factor to bring in nutrition.…”
Section: Eletion Of Immune Cells Through Fas (Cd95 Apo-1)-mediatedmentioning
confidence: 99%
“…Glioma U118(R) expressing a low level of FasL was established from U-118MG by transfection of a plasmid coding a FasL-specific ribozyme (17). U118(V), which served as the nonribozyme control, carries the EGFP-N1 vector (4). Overexpression of Fas (oFas) in MCF-7 cells was achieved by transfection of the oFas plasmid-encoding Fas gene under the control of CMV promoter.…”
Section: Cells and Reagentsmentioning
confidence: 99%